CYTOTOXIC AND GENOTOXIC EFFECT OF OXYTETRACYCLINE ON FISH CYPRINUS CARPIO AFTER ACUTE EXPOSURE: Toxic effect of oxytetracyclin on different organs of fish - MADHU SHARMA; JYOTI THAKUR; SUBHASH VERMA; PARDEEP SHARMA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Cytotoxicity in blood cells and genotoxic alteration in gill, liver, and kidney of Cyprinus carpio acutely (96 h) exposed to 80 mg/L oxytetracycline (OTC) including a control (non-exposed group) were evaluated in the present study. Genotoxic endpoints reflecting different types of genetic damage in cells of the liver, gill, and kidney were also determined by analysis of nuclear and cytoplasmic abnormalities. Methods: C. carpio was divided into two groups, one control and others treated with 80 mg/L OTC. After 96 h, sampling was done and slides were prepared for different tissues as well as for measuring polychromatic erythrocyte (PCE) frequency in blood. Slides were scored for micronucleus, nuclear abnormalities, swollen cells, and vacuolated cytoplasm. Results: The hereby data obtained showed a higher and significant increase in the genotoxic effect in all the tissues tested. Furthermore, gill cells showed the highest genotoxic effect followed by liver and kidney, while PCE frequency increases up to 72 h of exposure, on the other hand, a significant decrease in the value was observed at 96 h of exposure. Conclusion: The present study revealed that OTC has cytotoxic and genotoxic effect on different organs and blood cells of C. carpio at this concentration and suggests gill as sensitive tissue for genotoxic assessment.